One-Pot Assembly for Synthesis of 1, 4-Dihydropyridine Scaffold and Their Biological Applications. (19th August 2021) - Sharma, Mayank G.; Pandya, Juhee; Patel, Divyang M.; Vala, Ruturajsinh M.; Ramkumar, V.; Subramanian, Raghunandankumar; Gupta, Vivek K.; Gardas, Ramesh L.; Dhanasekaran, Anuradha; Patel, Hitendra M.
Abstract: A one-pot procedure for the preparation of functionalized 1, 4-dihydropyridines by three-component reaction using substituted heterocyclic aldehydes, ammonium acetate, and substituted β-ketoesters catalyzed by L-proline was described. Present protocol offers excellent yield up to 92%, flexibility with different substitution, convenient operation, and eco-friendliness. The synthesized products were confirmed by 1 H-NMR, 13 C-APT, and IR spectroscopy. Herein, final confirmation of the targeted motif was made by X-ray single-crystal analysis of representative compounds (4f, 4j, 4k, 4l, and 4o ). The chemically synthesized compounds were evaluated for the antiproliferative activity by cell viability (MTT) assay and dual AO/EB (acridine orange/ethidium bromide)-staining method against human A549 lung cancer cell lines. The viability of the treated cell was evaluated adopting MTT assay. According to associated changes in cell membranes during the process of apoptosis, a clear difference was observed between normal cells, early and late apoptotic cells, and necrotic cells. All compounds were found effective against Saccharomyces cerevisiae which was confirmed by increased reactive oxygen species production and DNA damage as compared to untreated yeast cell culture. Altogether, these compounds showed promising hope for application in pharmaceutical aid against yeast infections.